A study on factors contributing to customer preferances towards counterfeit product / Adderly Anak Sonti - Sonti, Adderly (2015)
The study aims to investigate which of the social and personality factors affects the attitude of the consumers towards counterfeit products. The study is also set out to examine the relationship of consumers’ attitude towards counterfeit product with purchase intention. A survey of 300 respondents was conducted in Serian, Sarawak. By having a better understanding of the consumers’ behavioral intentions of buying counterfeit products, the manufacturers and marketers of the genuine brand products can make better marketing strategies to entice the consumer to buy the original product and not the counterfeit version.